2014
DOI: 10.2169/internalmedicine.53.1364
|View full text |Cite
|
Sign up to set email alerts
|

Glycated Albumin (GA) is More Advantageous than Hemoglobin A1c for Evaluating the Efficacy of Sitagliptin in Achieving Glycemic Control in Patients with Type 2 Diabetes

Abstract: Objective The aim of this study was to compare the utility of hemoglobin A1c (HbA1c) and glycated albumin (GA) for evaluating the efficacy of the dipeptidyl peptidase-4 (DPP-4) inhibitor, sitagliptin, in patients with type 2 diabetes. Methods Sitagliptin (50 mg) was administered orally once daily in 67 outpatients with type 2 diabetes. Drug effectiveness was deemed present if the HbA1c or GA level decreased by 5% at week 4 and week 12 relative to the baseline value. Results The mean HbA1c level decreased from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…44,45 Since fructosamine reflects the average levels of blood glucose during the former 1 to 3 weeks, fructosamine would also expectedly mirror a poorly controlled glucose metabolism better than HbA1c. 40,46,47 Lindsey et al investigated fructosamine and HbA1c in a prospective, randomized, multicenter, controlled trial including 72 diabetic patients, 48 and showed that the combination of weekly fructosamine testing and daily blood glucose monitoring were no better than daily glucose monitoring alone. Subsequent studies demonstrated the utility of fructosamine and GA in diabetic patients who required tighter control, or in patients with conditions that rendered HbA1c testing unreliable such as gestational diabetes mellitus, postprandial hyperglycemia or gastric resection.…”
Section: Glycated Albumin and Fructosamine In Therapeutic Monitoring mentioning
confidence: 99%
See 1 more Smart Citation
“…44,45 Since fructosamine reflects the average levels of blood glucose during the former 1 to 3 weeks, fructosamine would also expectedly mirror a poorly controlled glucose metabolism better than HbA1c. 40,46,47 Lindsey et al investigated fructosamine and HbA1c in a prospective, randomized, multicenter, controlled trial including 72 diabetic patients, 48 and showed that the combination of weekly fructosamine testing and daily blood glucose monitoring were no better than daily glucose monitoring alone. Subsequent studies demonstrated the utility of fructosamine and GA in diabetic patients who required tighter control, or in patients with conditions that rendered HbA1c testing unreliable such as gestational diabetes mellitus, postprandial hyperglycemia or gastric resection.…”
Section: Glycated Albumin and Fructosamine In Therapeutic Monitoring mentioning
confidence: 99%
“…44,45 Since fructosamine reflects the average levels of blood glucose during the former 1 to 3 weeks, fructosamine would also expectedly mirror a poorly controlled glucose metabolism better than HbA1c. 40,46,47…”
Section: Clinical Studies About Glycated Albumin and Fructosaminementioning
confidence: 99%
“…Glycated albumin has been shown to change faster than HbA1c in response to changes in medication or exercise. 67,68 Compared to HbA1c, glycated albumin is more strongly correlated with continuous glucose measurements over 1 to 2 days, 69,70 and may more accurately reflect long-term glycemic variability and glucose excursions. 71,72 …”
Section: Clinical Utility Of Nontraditional Markers Of Hyperglycemiamentioning
confidence: 99%
“…Furthermore, the agent provides improvements in glycemic control [17]. DPP-4 inhibitors-related studies on humans have found a decrease in HbA1c levels [18]. It has been reported that DPP-4 inhibitors do not affect body weight [19].…”
mentioning
confidence: 99%